Design of chest retractor assembly for paediatric cardiothoracic surgery - Neo, Ivan Tjin Ho (2013)
The engineering in medical and surgical industry is mostly established for the wider population. The same tools or apparatus that may be used in a surgical procedure for an adult, may not be available or applicable, to be used in a surgical procedure for paediatric group patients, including infants and those neonates. In the case for cardiothoracic surgery for paediatric patients, a retracting device which is used to optimise the visual field of surgical procedure is currently limited. The current practice involves the first assistant manually using a retractor, retractor blade or sutures to optimise this surgical field and maintain a desired retracted state, whilst assisting the surgeon with other tasks, such as the suction of blood during the surgery. This report involves a design of such a chest retractor, which would allow for the desired retracted state to be realised. The design procedure required the control of variables such as the weight that the retractor needed to support and the dimensions it needed to adhere to. The methods used in the design involved 3-D modelling, finite element simulations and prototype construction. The completion of this prototype would allow the surgeon to carry out his procedures in a more stable environment, and free the first assistant from having to maintain the retracted state, and would allow the first assistant to better assist the surgeon in other tasks.